1975
DOI: 10.1590/s0071-12761975000100012
|View full text |Cite
|
Sign up to set email alerts
|

Acumulação diferencial de nutrientes por cinco cultivares de milho (zea mays L): II - acumulação de micronutrientes

Abstract: RESUMONo presente trabalho, os autores apresentam os resultados de um ensaio de campo empregando os cultivares Agroceres 256, Agroceres 504, Centralmex, H-7974 e Piranao no sentido de aquilatar diferenças na acumulação e exportação de micronutrientes. O ensaio foi conduzido num regossol de fertilidade mediana, exceto em relação ao Κ que é baixo, situado no município de Piracicaba, SP. O delineamento experimental utilizado foi de blocos ao acaso com 4 repetições. Foram seguidas as prá-ticas culturais comuns e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

1977
1977
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
1
0
3
Order By: Relevance
“…High investment environment in fertilization promoted greater Mn accumulation starting in V5; the total extraction in the physiological maturation was 778 and 500 g ha -1 in the environments of high and medium investment, respectively (Table 3). These quantities are below the 900 g ha -1 quantified by Karlen et al (1988); however, close to the values obtained by Duarte et al (2003) and Andrade et al (1975b), of 638 g ha -1 and 496 to 720 g ha -1 , respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…High investment environment in fertilization promoted greater Mn accumulation starting in V5; the total extraction in the physiological maturation was 778 and 500 g ha -1 in the environments of high and medium investment, respectively (Table 3). These quantities are below the 900 g ha -1 quantified by Karlen et al (1988); however, close to the values obtained by Duarte et al (2003) and Andrade et al (1975b), of 638 g ha -1 and 496 to 720 g ha -1 , respectively.…”
Section: Resultssupporting
confidence: 83%
“…These results are in agreement with Bender (2013), which reported that in the period before flowering only half of the total Cu accumulation has occurred. Maximum Cu extraction point determined by Andrade et al (1975b) was between 101 and 108 days after emergence, and Borges et al (2009) at 102 days after emergence. Confirmation of Cu extraction pattern extending to the end of the cycle indicates that, regardless of the hybrid used and the growing environment, ensuring conditions for satisfactory supply of this micronutrient, also during the grain filling stage of the crop, are important.…”
Section: Resultsmentioning
confidence: 95%
“…Segundo Tukey et alii (1958) mencionado por ANDRADE (1975), o Mn é um dos elementos que pode ser lavado das folhas, acarretando perdas deste nutriente durante o cifclo vegetativo. CAMARGO (1970., assinala que a lavagem varia com a natureza do material vegetal, e com a espécie de planta.…”
Section: Manganêsunclassified
“…y = -0,00000x 2 + 0,003x -0,004; R 2 = 0,91 y = -0,000004x 2 + 0,002x -0,003; R 2 = 0,90 y = 0,00002x 2 + 0,002x -0,004; R 2 = 0,95 y = 0,0002x 2 -0,001x -0,007; R Em todas as doses de enxofre estudadas, constatou-se a seguinte ordem de acúmulo de micronutrientes na parte aérea de plantas de milho: Fe>Mn>Zn>Cu. Concordando com os resultados obtidos por Andrade (1975b) estudando a marcha de absorção dos micronutrientes cobre, ferro, manganês e zinco em plantas de milho, observou a mesma sequência de acúmulo desses micronutrientes na parte aérea do milho.…”
Section: G) Micronutrientesunclassified